Endurance Training and Cardiovascular Health: Mechanism and Clinical Implications - Rokicki, Sebastian; Skoczylas, Kamila; Schok, Katarzyna; Mikulska, Julia (Journal of Education, Health and Sport, 2023)
Introduction and objective: Cardiovascular diseases are the leading cause of death worldwide, but regular physical activity can help reduce the risk of heart disease. Intensive endurance training brings many undeniable benefits but recently there have been scientific studies regarding potential complications that this type of physical activity may cause. This publication attempts to analyze whether the intensity of endurance training can reach a level at which it becomes harmful to the health of athletes. Materials and methods: This article reviews the literature on the impact of physical activity on cardiovascular health, with particular emphasis on endurance training. Articles were searched by key words, e.g. endurance training, cardiovascular health, marathon, running, cycling in various configurations, in Pubmed, Medline, Google Scholar databases. Actual state of knowledge: Regular physical activity is commonly regarded as the best preventive factor for cardiovascular diseases. Intensive endurance training significantly increases the efficiency of the cardiovascular system. Despite the significant benefits of regular endurance training, scientific reports suggest that athletes practicing this type of activity are more prone to developing certain cardiovascular disorders, such as coronary heart disease, atrial fibrillation, sinus bradycardia, and myocardial fibrosis. Colclusion: Regular and moderate aerobic physical activity is key to maintain optimal health. Endurance athletes develop a series of adaptations in the cardiovascular system, exhibit greater survival rates, and are less likely to experience sudden cardiac death compared to those who do not engage in regular physical activity. There is evidence suggesting a higher incidence of certain cardiovascular complications compared to healthy individuals who do not engage in sports. The reasons for these changes and their impact should be the subject of further research.